Conservation of fishes in the Elands River, Mpumalanga, South Africa: Past, present and future - Gordon C. O’Brien; Nico J. Smit; Victor Wepener (Koedoe: African Protected Area Conservation and Science, 2014)
In an isolated reach, between two large natural waterfalls in the Elands River in Mpumalanga, populations of a critically endangered Kneria sp., the endangered Chiloglanis bifurcus and a genetically unique population of Labeobarbus polylepis occur. The aim of this article was to evaluate past efforts to conserve these fishes, describe the current status and propose future conservation and management actions. The population status assessments were based on a series of fish community composition and population structure evaluations from surveys undertaken at 22 sites during seven surveys from 2002 to 2006. Although water-use activities have continued to increase in the area, impacts have been offset by conservation efforts initiated almost 30 years ago. The existing C. bifurcus population appears to be stable, which is reflected in the downgrading of the conservation status of the species from critically endangered to endangered. The abundance of the kneriid population appears to be increasing and spreading to other tributaries in the study area. The abundance of L. polylepis appears to be increasing but has still not reached historical levels. Conservation implications: Continued conservation efforts are required to protect these fishes. This case study presented a rare example of how the impacts associated with the use of aquatic resources in South Africa can successfully be offset by conservation efforts.